2011
DOI: 10.1080/08927014.2011.619657
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by the yeastRhodotorula mucilaginosa: process, repeatability and cell attachment in a continuous biofilm reactor

Abstract: Yeast biofilms contribute to quality impairment of industrial processes and also play an important role in clinical infections. Little is known about biofilm formation and their treatment. The aim of this study was to establish a multi-layer yeast biofilm model using a modified 3.7 l bench-top bioreactor operated in continuous mode (D = 0.12 h(-1)). The repeatability of biofilm formation was tested by comparing five bioprocesses with Rhodotorula mucilaginosa, a strain isolated from washing machines. The amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous studies could show that organisms that were isolated from biofilms from washing machines are more tolerant to chemical detergents compared to control strains [8,15]. For this reason potential drug-resistant organisms, which have been identified in the domestic environment, imply a potential health risk due to cross-contaminations during the washing process.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies could show that organisms that were isolated from biofilms from washing machines are more tolerant to chemical detergents compared to control strains [8,15]. For this reason potential drug-resistant organisms, which have been identified in the domestic environment, imply a potential health risk due to cross-contaminations during the washing process.…”
Section: Introductionmentioning
confidence: 99%
“…The high hydrophobicity of Rhodotorula cells in M2 medium (with additional supplementation with yeast extract) may be connected to the accumulation of extracellular substances on the yeast cell surface. Gattlen et al ( 2011 ) reported that biofilm formed by R. mucilaginosa cells over 6 days, isolated from washing machines, also contained proteins and polysaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…In beer, yeast biofilms constitute a negative phenomenon. In breweries, yeast can form biofilms colonizing new surfaces or existing fungal or bacterial biofilms (Gattlen et al 2011 ). In particular, yeasts have a high impact on alcohol-free beer and beer-mixed beverages, where they can be responsible for up to 90% of the spoilage incurred (Riedl et al 2019 ).…”
Section: Yeast Biofilm In Food Realmsmentioning
confidence: 99%